Physics design of the HNB accelerator for ITER. (21st August 2015) - de Esch, H.P.L.; Kashiwagi, M.; Taniguchi, M.; Inoue, T.; Serianni, G.; Agostinetti, P.; Chitarin, G.; Marconato, N.; Sartori, E.; Sonato, P.; Veltri, P.; Pilan, N.; et al.
Abstract: The physics design of the accelerator for the heating neutral beamline on ITER is now finished and this paper describes the considerations and choices which constitute the basis of this design. Equal acceleration gaps of 88 mm have been chosen to improve the voltage holding capability while keeping the beam divergence low. Kerbs (metallic plates around groups of apertures, attached to the downstream surface of the grids) are used to compensate for the beamlet–beamlet interaction and to point the beamlets in the right direction. A novel magnetic configuration is employed to compensate for the beamlet deflection caused by the electron suppression magnets in the extraction grid. A combination of long-range and short-range magnetic fields is used to reduce electron leakage between the grids and limit the transmitted electron power to below 800 kW.